2015
DOI: 10.17221/8415-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sex, age and season on the haematological profile of alpacas (Vicugna pacos) in Central Europe

Abstract: ABSTRACT:The aim of this study was to establish reference intervals for the haematological profile of alpacas on the basis of a large population of clinically healthy animals, and to determine the influence of sex, age and season on these indicators. Blood samples were collected from 243 alpacas (53 males and 156 females over six months of age and 34 crias -12 males and 22 females -under six months of age). The selected farms were located in Central Europe (Czech Republic and Germany). We determined 13 haemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…In the case of the quantity of immune system cells -lymphocytes, granulocytes and monocytes (Zapata et al 2003) -the same study indicated that the season only slightly affects the quantity of such cells, and the impact was not statistically significant. Very similar results to the results obtained for guanaco (Zapata et al 2003) in respect of the quantity of lymphocytes, granulocytes and monocytes were obtained for mammals from the camelid family -alpaca (Husakova et al 2015), where a slight impact of the season was also observed in respect of the quantity of such cells.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…In the case of the quantity of immune system cells -lymphocytes, granulocytes and monocytes (Zapata et al 2003) -the same study indicated that the season only slightly affects the quantity of such cells, and the impact was not statistically significant. Very similar results to the results obtained for guanaco (Zapata et al 2003) in respect of the quantity of lymphocytes, granulocytes and monocytes were obtained for mammals from the camelid family -alpaca (Husakova et al 2015), where a slight impact of the season was also observed in respect of the quantity of such cells.…”
Section: Introductionsupporting
confidence: 86%
“…2009) and activity (Nowaczyk et al 2005 of lymphocytes and granulocytes, and the quantity of monocytes (Jacobson et al 1978, Nowczyk et al 2005, Cetin et al 2009) in peripheral blood, and thus these cells are subject to apoptosis. Such an interdependency was also observed in farm animals (cattle), where the impact of the season was recorded in respect of immune system cells (Deptuła et al 1992, Deptuła andDorynek 1993) and their activity (Deptuła et al 1992, Deptuła andDorynek 1993) in phagocytosis, and in the quantity of serum immunoglobulins and total protein; a slight seasonal impact was also reported in respect of the quantity of lymphocytes, granulocytes and monocytes in biungulates from the camelid family, including alpaca (Husakova at al. 2015) and guanaco (Zapata et al 2003) and, in the case of the latter, also in respect of total protein volume (Zapata et al 2003).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…In the animals in our study, no differences in PCV were found with respect to age or gender. However, other authors showed that male SAC usually have higher PCV than females [ 54 , 55 ]. This could be due to the fact that our study did not investigate homogeneous groups, but rather data from animals with different pathological conditions.…”
Section: Discussionmentioning
confidence: 97%